“Do I really recognize it?” Delving into English Language Learners’ Identity Construction - Mudra, Heri (Universitas Islam Negeri Walisongo Semarang, 2024)
Learners must construct a learning identity to succeed when learning English. This current study attempted to discuss English language learners’ (ELLs) insights on language learning identity construction. A survey study collected quantitative data from 219 ELLs in several Indonesian universities. Questionnaires were distributed and completed via online mode (i.e., Google Forms), and a two-week due time was assigned for each participant. As for results, various insights emerged as the ELLs recognized their identity construction. They have identity aspects such as linguistics, belongingness, expectation, attitude, and agency. Each aspect helped to form ELLs’ identity construction in many ways, including learning competence, socio-cultural awareness, educational component, and psychological conviction. Identity construction is not complicated to achieve as long as ELLs have strong learning commitment. In addition, it is implied that this study is paramount to empower pedagogical strategies, educational policies, and academic performance.